(untitled) (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
The origin of eukaryotes is understood as one of the most important issues in the history of living beings. There are several points of view to seek a broad understanding of the eukaryote origins, which encompass paleontological data, energetics, eukaryote-particular characteristics origins or the connections among dissimilar eukaryotic groups. Many proposals of endosymbiotic theory have been presented to explain the origin of eukaryotes and their mitochondria. Only recently, energy and the energetic constraints started to be considered by endosymbiotic theory to understand the contribution of prokaryotic cell organization to cell history, acknowledging that only cells that possessed mitochondria had the bioenergetic assets to achieve eukaryotic cell complexity, which explains why no in between beings existed in the prokaryote-to-eukaryote transition. This study attempts to approach the eukaryote origins from the standpoint of constructal theory, i.e., “For a flow system to persist in time (to survive), it must evolve in such a way that it provides easier and easier access to the currents that flow through it.” Therefore, the explanation is based on the direction of evolution in time, in which it has been introduced the thought that system structure should morph freely towards the optimal architecture and flow organization that minimize resistances to the internal flows (exergy losses) that are required for the system existence, which is proposed as the origin of eukaryotes, mitochondria, chloroplasts, and for the origin of the eukaryotic nucleus.